Identification of available and desirable indicators for patent systems, patenting processes and patent rights: research project for the German Patent and Trademark Office - Stefan Lachenmaier (ifo Institut für Wirtschaftsforschung an der Universität München, 2005)
In 2004 the German Patent and Trademark Office commissioned the Ifo Institute to deliver a research report on the topic "Identification of Available and Desirable Indicators for Patent Systems, Patenting Processes and Patent Rights". - The report provides an extensive overview of the existing literature about the valuation of patents, mainly from an economic point of view but also giving consideration to legal and business aspects. This includes the valuation of the patent system itself, the valuation of the patenting process and the valuation of the assigned patent rights. Looking at the relevant literature, however, it reveals immeadiately that a quantification of these patent related issues is not easy. The economic literature relies heavily on the valuation of patent rights, as this gives a possible measurement of innovation output.
Keywords: O34; 330; Patent; Patentrecht; Markenrecht; Deutschland; Patent; Patentrecht; Bewertung; Wirtschaftsindikator; Theorie; Deutschland